Somatic mutations and outcomes in chronic myeloid leukemia adolescent and young adults compared to children, adults, and BCR::ABL1-positive acute lymphoblastic leukemia - Krizkova, Jitka; Polivkova, Vaclava; Laznicka, Adam; Curik, Nikola; Benesova, Adela; Suchankova, Pavla; Smazik, Tomas; Vysinova, Veronika; Mikulenkova, Dana; Klamova, Hana; Markova, Marketa Stastna; Srbova, Dana; et al. (Leukemia, 2025)
Adolescent and young adults (AYAs) with chronic myeloid leukemia in chronic phase (CML-CP) reportedly respond worse to tyrosine kinase inhibitors (TKIs) than adults, potentially due to additional genetic abnormalities, including mutations in cancer-related genes (CRGs). This real-life study compared mutation profiles and their impact on outcomes in 80 AYA, 97 adult, and 16 pediatric CML-CP patients, alongside 81 BCR::ABL1-positive acute lymphoblastic leukemia (Ph+ ALL) patients. CRG mutations were more frequent in AYAs (25.0%) than in adults (19.6%) or children (12.5%). AYAs with Ph+ ALL exhibited higher mutational frequencies (53.3%) compared to children (26.7%) and adults (38.9%). At diagnosis, mutations in ASXL1, DNMT3A, and TET2 dominated in CML-CP and RUNX1, IKZF1, and BCR::ABL1 in Ph+ ALL. ASXL1 mutations correlated with reduced progression-free survival (PFS) in AYAs and adults. Unlike adults, AYAs showed no increase in BCR::ABL1 kinase domain mutations during TKI therapy. Nilotinib improved PFS in AYAs with ASXL1 mutations, highlighting the efficacy of higher-generation TKIs. ASXL1 mutations also impaired erythropoiesis, warranting further validation. Despite a higher mutational burden, AYAs did not exhibit worse prognoses than adults. Lower mutation rates at follow-up suggest potential impact of nilotinib. Mutation profiling and optimized TKI use are crucial to mitigate progression risks in CRG-mutated patients.
Keywords: Young Adult; bcr-abl fúzní proteiny; Fusion Proteins, bcr-abl; Male; mutace; protoonkogenní proteiny c-abl; mladý dospělý; chronická myeloidní leukemie; Adolescent; následné studie; prognóza; Child; dítě; Adult; dospělí; mužské pohlaví; inhibitory proteinkinas; akutní lymfatická leukemie; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mladiství; Follow-Up Studies; lidé; ženské pohlaví; Biomarkers, Tumor; Humans; Protein Kinase Inhibitors; Prognosis; Mutation; Proto-Oncogene Proteins c-abl; Female; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé středního věku; nádorové biomarkery; Middle Aged